2003
DOI: 10.1128/mcb.23.24.9104-9116.2003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the Cyclin A Gene by the Architectural Transcription Factor HMGA2

Abstract: The HMGA2 protein belongs to the HMGA family of architectural transcription factors, which play an important role in chromatin organization. HMGA proteins are overexpressed in several experimental and human tumors and have been implicated in the process of neoplastic transformation. Hmga2 knockout results in the pygmy phenotype in mice and in a decreased growth rate of embryonic fibroblasts, thus indicating a role for HMGA2 in cell proliferation. Here we show that HMGA2 associates with the E1A-regulated transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 46 publications
3
112
0
Order By: Relevance
“…In contrast to HMGA1, the role of HMGA2 as an architectural transcription factor is less well studied. To our knowledge, to date, besides Imp2, only five other genes have been identified as target genes of HMGA2, being the CDC2, TK1, and cyclin E genes (34); the DNA repair gene ERCC1 (21); and the cyclin A gene, which is a key factor in cell cycle control (35). In the two latter cases, it has been shown that HMGA2 binds to AT-rich regions in the promoter of these target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HMGA1, the role of HMGA2 as an architectural transcription factor is less well studied. To our knowledge, to date, besides Imp2, only five other genes have been identified as target genes of HMGA2, being the CDC2, TK1, and cyclin E genes (34); the DNA repair gene ERCC1 (21); and the cyclin A gene, which is a key factor in cell cycle control (35). In the two latter cases, it has been shown that HMGA2 binds to AT-rich regions in the promoter of these target genes.…”
Section: Discussionmentioning
confidence: 99%
“…This gene (CCNA) has not yet been described as a target for let-7b. However, HMGA2, which is a known target of let-7b [18], is a major activator of cyclin A expression [19]. Cyclin A downregulation might thus occur indirectly via let-7b/HMGA2 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by us and other groups have shown that aberrant expression of architectural transcription factor HMGA2 is associated with the regulation of cell proliferation and gene expression (8,19,20,23,24). We therefore sought to screen for novel HMGA2-interacting proteins that mediate the pleiotropic effects by HMGA2.…”
Section: Hmga2 Is Sumoylated In Vitro and In Vivomentioning
confidence: 99%